Incremental temperature cement delivery technique may prevent cement leakage in metastatic vertebral lesions. (15th November 2017) - Liu, Hao; Wang, Shenghao; Liu, Tao; Meng, Bin; He, Fan; Zhou, Rong; Yang, Huilin
Objectives: To analyze the clinical efficacy and cement leakage rate of percutaneous kyphoplasty (PKP) for the treatment of metastatic vertebral lesions between the two groups using different cement infusion techniques. Methods: One hundred twenty-nine patients (160 metastatic vertebral fractures) who chose "the incremental temperature cement delivery technique" (ITCDT group) and 105 patients (128 metastatic vertebral fractures) who chose "traditional infusion technique" (TI group) were finally enrolled (nine patients were lost to the follow-up). The visual analog scale (VAS), Oswestry Disability Index (ODI), the local Cobb's angle, the relative height of the vertebral anterior border, and cement leakage were analyzed to evaluate the clinical efficacy of the two cement infusion techniques within postoperative 12 months. Results: There was no significant difference in the VAS scores, ODI scores, the relative height of the vertebral anterior border, and local Cobb's angle between the ITCDT group and TI group preoperatively and postoperatively ( p > 0.05). The cement leakage occurred in three patients of ITCDT group (2.3%), which was significantly less than TI group (12 patients, 11.4%; p < 0.05). Conclusions: The ITCDT and TI technique in kyphoplasty are effective at relieving pain and improving functional disability, vertebral height, and kyphosis angle; However, kyphoplasty using the ITCDT causes less cement leakage significantly.